OsteoKnee® - Lai, K.W. (University of Malaya, 2015)
Osteoarthritis (OA) is a degenerative joint disease that commonly occurs in knee joint, which has become the leading cause of disability in a few countries.OsteoKnee  is a device for early detection and prediction of OA through knee sound detection and knee intra-articular pressure (knee effusion) for clinical practice. This is new, non-invasive, portable, radiation-free, and relative inexpensive approach for assessing and monitoring knee joint in clinical practice. This trademark registered in class 10 and 44